(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this article, we proposed a comprehensive pest control model that integrated both delay differential equations and stochastic processes to mitigate the spread of whiteflies in coconut plantations. The delay model introduced a time lag in the implementation of awareness programs and investigated its impact on the system’s equilibrium stability. Numerical simulations validated the model’s effectiveness in enhancing pest management. A stochastic component, formulated using a Wiener process within a system of non-linear ordinary differential equations (ODEs), was used to estimate the probability of disease elimination under environmental fluctuations. The study was novel in combining both deterministic delays and stochastic effects in a unified framework, offering deeper insights into timing and control efficiency. Although focused on coconut farming, the modeling approach and techniques had broader applicability in agricultural pest control scenarios. The findings enhanced our understanding of pest dynamics under uncertainty and delay, providing a foundation for more informed and effective control interventions in agricultural ecosystems.